Formulation selection of aliphatic aromatic biodegradable polyester film exposed to UV/solar radiation - Kijchavengkul, Thitisilp; Auras, Rafael; Rubino, Maria; Selke, Susan; Ngouajio, Mathieu; Fernandez, R. Thomas (Polymer degradation and stability, 2011)
Aliphatic aromatic copolyester films, poly(butylene adipate- co-terephthalate) or PBAT, are susceptible to photodegradation, leading to main chain scission and crosslinking. The presence of crosslinked structures not only decreased the mechanical properties of the film due to embrittlement, but also hindered the biodegradation process by limiting access of water and microorganisms to the polymer chains. This has limited the use of PBAT for outdoor applications, such as mulch films. In this study, response surface methodology (RSM) was used to determine the optimal concentrations of carbon black (CB) and the chain breaking antioxidant butylated hydroxytoluene (BHT) for the design of mulch films that can prevent the formation of crosslinked structures from recombination of free radicals. An overlaid contour plot of suitable concentrations of CB and BHT for the formulation of mulch film for crop production in Michigan or regions with similar solar radiation was established using selection criteria of light transmission of less than 20%, final tensile strength of at least 6.35 MPa, maximum gel fraction of 0.30, and positive number average molecular weight reduction sensitivity in the early stage of degradation.